An endogene-resembling transgene delays the onset of silencing and limits siRNA accumulation - Dadami, Elena; Moser, Mirko; Zwiebel, Michele; Krczal, Gabi; Wassenegger, Michael; Dalakouras, Athanasios (FEBS letters, 2013)
In plants, transgenes are generally more sensitive against RNA silencing than endogenes are. In this study, we generated a transgene that structurally mimicks an endogene. It is composed of endogenous promoter, 5′-UTR, introns, 3′-UTR and terminator elements. Our data revealed that, in contrast to a conventional transgene, an endogene-resembling transgene was more stably expressed and poorly processed into small RNAs. In addition, although both constructs triggered methylation of homologous DNA sequences at similar levels, the endogene-resembling transgene exhibited significantly delayed onset of local and systemic silencing.